Inhibiting aberrant seizure-induced neurogenesis by temozolomide improves cognitive impairments associated with long-term amygdala kindling - Francis, Travis J.; Reive, Brady S.; Lehmann, Hugo; Fournier, Neil M. (Frontiers in Neuroscience, 2025)
In the adult dentate gyrus, new neurons are continuously generated and integrated into the existing circuitry where they play a crucial role in maintaining important functions related to learning and memory. Seizures not only robustly increase levels of hippocampal neurogenesis but can also induce aberrant migration and functional development of these new neurons, which has been hypothesized to promote network excitability and epileptogenesis. However, the contribution of new neurons to the development of epilepsy-related cognitive impairments remain unclear. Here, we investigated whether suppressing this abnormal elevation in neurogenesis that occur with seizures could prevent the emergence of cognitive dysfunction and behavioral deficits associated with chronic epilepsy. Using the long-term amygdala kindling model (consisting of 99 electrical stimulations), we demonstrate that initiating cyclic treatment with the DNA-alkylating agent temozolomide (TMZ) during a period of heightened neurogenic activity can reduce aberrant hippocampal neurogenesis and rescue impairments in a contextual fear discrimination task known to depend on functional neurogenesis. In addition, TMZ treatment also prevented object recognition memory deficits after kindling. Together, our findings suggest kindled seizures trigger the production of new neurons that can effectively rewire and interfere with hippocampal circuit function which can contribute to the development of chronic cognitive and behavioral deficits as seen in both patients with epilepsy and other rodent models. Thus, strategies that can selectively reduce aberrant adult neurogenesis may serve as a novel approach to treat cognitive deficits associated with epilepsy.